2017
DOI: 10.3389/fimmu.2017.00515
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Anaphylactic Routes: The Potential Role of Macrophages

Abstract: Anaphylaxis is an acute, life-threatening, multisystem syndrome resulting from the sudden release of mediators from effector cells. There are two potential pathways for anaphylaxis. The first one, IgE-dependent anaphylaxis, is induced by antigen (Ag) cross-linking of Ag-specific IgE bound to the high-affinity IgE receptor (FcεRI) on mast cells and basophils. The second one, IgG-dependent anaphylaxis is induced by Ag cross-linking of Ag-specific IgG bound to IgG receptors (FcγRI, FcγRIIA, FcγRIIB, FcγRIIC, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 64 publications
0
23
0
Order By: Relevance
“…Notwithstanding, two key factors could play critical roles in macrophage responses. The first is the nature of the responding macrophage receptor, and its associated signaling threshold, that may regulate the transitional link between robust internalization and kinetics of bioactive molecule release from macrophages (Escribese et al, 2017;Moghimi, 2018). For example, a plausible role for low-affinity Fc-receptor-mediated response to nanomedicine anaphylaxis has been proposed (Moghimi, 2018).…”
Section: Innate Immunity and Nanoparticle Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding, two key factors could play critical roles in macrophage responses. The first is the nature of the responding macrophage receptor, and its associated signaling threshold, that may regulate the transitional link between robust internalization and kinetics of bioactive molecule release from macrophages (Escribese et al, 2017;Moghimi, 2018). For example, a plausible role for low-affinity Fc-receptor-mediated response to nanomedicine anaphylaxis has been proposed (Moghimi, 2018).…”
Section: Innate Immunity and Nanoparticle Performancementioning
confidence: 99%
“…Indeed, Fc receptors (FcgRI, FcgRIIA, FcgRIIB, FcgRIIC, FcRIIIA, and FcgRIIIB) show different affinities for antibodies and exhibit different expression patterns and downstream signaling (Strait et al, 2002). Fc receptors also contribute to desensitization (Strait et al, 2002;Escribese et al, 2017). Nevertheless, the location of responding macrophages, their number, and accessibility to nanoparticles play a role as a rate-limiting factor.…”
Section: Innate Immunity and Nanoparticle Performancementioning
confidence: 99%
“…The first limitation is that it is still unknown whether BP21 could be an effective therapeutic agent for human anaphylaxis as well as mouse anaphylaxis. There are two potential pathways (IgE‐dependent and IgE‐independent) for anaphylaxis . IgE‐dependent anaphylaxis is the classical and main pathway induced by an antigen (at low concentration) cross‐linked by its specific IgE bound to the high‐affinity IgE receptor (FcεRI) on mast cells and basophils, followed by the release of histamine.…”
Section: Discussionmentioning
confidence: 99%
“…IgG‐dependent (IgE‐independent) anaphylaxis is an alternative pathway induced by an antigen (at high concentrations of antigen and IgG) cross‐linked by its specific IgG bound to IgG receptors (FcγRI, FcγRIIA, FcγRIIB, FcγRIIC, and FcγRIIIA) rather than IgE, which are present on macrophages and neutrophils instead of mast cells, followed by the release of mainly PAF instead of histamine. Mouse models of anaphylaxis indicated that both the IgG‐dependent pathway as well as IgE‐dependent pathway are important for anaphylaxis, but their importance in human anaphylaxis is not yet clear . However, in humans, recent studies have shown that PAF induces wheal‐and‐flare reactions in skin and that circulating PAF levels are direct and the activities of circulating PAF‐AH, which degrades PAF to inactive lyso‐PAF, are inversely correlated with the severity of anaphylaxis in humans .…”
Section: Discussionmentioning
confidence: 99%
“…One explanation could be that mast cells can selectively release serotonin without releasing histamine ( 52 ) via high-affinity serotonin-binding proteins used to sequester serotonin from secretory vesicles ( 53 ). Serotonin functions as a regulator of immune and inflammatory responses and is partially mediated through direct interactions with macrophages ( 54 ).…”
Section: The Contact System Integrates With Activated Mast Cells Thementioning
confidence: 99%